The fire at Mary Anne's house - Martin, Ann M., 1955- (New York : Scholastic, 1999)
Mary Anne tries to rebuild her life after everything she owns is destroyed in a house fire.
"An Apple paperback.".
5.8
3-6
Keywords: Babysitting -- Fiction; Disasters -- Psychological aspects -- Fiction; Friendship -- Fiction; Babysitting -- Fiction; Disasters -- Psychological aspects -- Fiction; Friendship -- Fiction